Hybrid and Virtual Learning: Bridging the Educational and Digital Device - Lee Bih Ni (Malaysian Journal of Social Sciences and Humanities, 2023)
This paper discusses hybrid and virtual learning. Management & Science University (MSU) will emphasize hybrid and virtual learning as one of the university's learning components. The highlights of this study use basic elements that contain background information, discussion of the information found, and conclusions from the sources of information. The emphasis on hybrid and virtual learning was made after his side saw changes in the landscape of higher education after the COVID-19 epidemic hit the world. This study uses the synthesis method. The results of this study found that before COVID-19, the focus was only on full-time and face-to-face learning. However, when the pandemic occurs, we build expertise to enable hybrid and virtual learning. It is also believed that it provides convenience to working individuals because they do not need to come to campus post-pandemic. It is also widely implemented in universities and schools in the West.